1997
DOI: 10.1046/j.1365-2826.1997.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Substance P‐Immunoreactive Nerve Fibres in the Anterior Pituitary to Plasma Oestrogen Levels in the Rat

Abstract: The mammalian anterior pituitary has recently been shown to be innervated by substantial amounts of peptidergic nerve fibres. It has also been found that adrenalectomy increases the amount of calcitonin gene-related peptide-like immunoreactive nerve fibres in the anterior pituitary of the rat, and that stimulation of the nerve fibres in vitro can enhance release of ACTH. In the present study, the density of substance P-like immunoreactive nerve fibres in the anterior pituitary of the rat were examined in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…Estrogen treatment in other experimental paradigms has also been reported to differentially regulate SP and CGRP. For example, in the anterior pituitary and hypothalamus, estrogen treatment downregulates SP expression but upregulates CGRP expression (Brown et al 1990; Gon et al 1990; O'Halloran et al 1990; Herbison and Theodosis 1992; Ma et al 1997a). While some studies have shown an increase in CGRP in the DRG by estrogen treatment (Gangula et al 2009) it has also been reported that estrogen can reduce CGRP (Yang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen treatment in other experimental paradigms has also been reported to differentially regulate SP and CGRP. For example, in the anterior pituitary and hypothalamus, estrogen treatment downregulates SP expression but upregulates CGRP expression (Brown et al 1990; Gon et al 1990; O'Halloran et al 1990; Herbison and Theodosis 1992; Ma et al 1997a). While some studies have shown an increase in CGRP in the DRG by estrogen treatment (Gangula et al 2009) it has also been reported that estrogen can reduce CGRP (Yang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In other neural systems, estrogen has been shown to have a negative effect on SP expression. For example, estrogen treatment has been shown to decrease SP levels in the anterior pituitary (Brown et al 1990; O'Halloran et al 1990; Ma et al 1997a). In neurons of the bed nucleus of the stria terminalis, as well as those in the ventromedial nucleus of cycling female rats, SP immunoreactivity is lowest during proestrus, when estrogen levels are high (Micevych et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In the dog, the synapses are found on corticotropes and somatotropes whereas, in the rat, they can be found on every hormone‐secreting cell type (11–13). Moreover, changes in endocrine status by adrenalectomy or ovariectomy in the rat can profoundly increase the density of the nerve fibres in the anterior pituitary (14, 15). Following adrenalectomy, the increase in immunoreactive nerve fibres is a result of active axonal sprouting (16), and the growth cones of the sprouting nerve fibres appear to favour the corticotropes (17).…”
mentioning
confidence: 99%
“…It has been found that adrenalectomy or ovariectomy in the rat induces significant increases in immunoreactive nerve fibres in the anterior pituitary. 19,20 Because the increase in immunoreactive nerve fibres can be due either to an increase in peptide content in pre-existing nerve fibres, so as to render them detectable by immunohistochemistry, or to an actual increase in the number of nerve fibres. GAP-43 immunoreactivity has been studied.…”
Section: Are the Nerve Fibres Functionally Important Or Are They Redumentioning
confidence: 99%